Functional assessments used by occupational therapists with older adults at risk of activity and participation limitations: a systematic review and evaluation of measurement properties - Wales Kylie (Systematic Reviews, 2012)
Abstract Background Older adults experience activity and participation limitations that are associated with ageing. Activity and participation limitations affect an older adult’s ability to engage in meaningful daily activities and valued life roles. Occupational therapists provide interventions to reduce such limitations and monitor client change to ensure that interventions are effective. Client change should be measured through the use of valid and reliable assessments. Yet occupational therapists can favour the use of non-standardised assessments leading to inaccurate reflections of client change and difficulties in comparing the effectiveness of interventions. A number of reasons have been suggested as to why therapists may favour non-standardised assessments, including a lack of knowledge (of assessments and their properties) and lack of skill. Methods/design This paper describes the systematic review protocol that will be used to identify functional assessments used in randomised trials of occupational therapy interventions for older adults (≥70 years of age). Interventions will focus on enhancing functional independence for either older adults transitioning from hospital to home, or community dwelling older adults. We will search Medline, EBSCO and OTseeker using a pre-determined search strategy to identify Functional assessments. These assessments will be recorded and, in phase two, their measurement properties analysed. Discussion This protocol provides a comprehensive guideline for conducting the proposed systematic review. The results of this systematic review will provide a thorough and unbiased identification and evaluation of measurement properties of functional assessment tools used in randomised trials to evaluate occupational therapy intervention. This information can be used to determine which assessment has superior measurement properties and will inform occupational therapy practice.